The Influence of Influencer Marketing and Online Customer Reviews on Purchase Intention Through the Perceived Value of Cosmetic Products on Tiktok Shop (An Empirical Study on Students in the City of Pekanbaru) - Azzahra Azzahra; Awliya Afwa; Moniko Moniko (UNIVED Press, 2024)
This research aims to determine the extent of the influence of influencer marketing and online customer reviews on purchase intention through the perceived value of Tiktok Shop cosmetic products. This study consists of two independent variables, namely influencer marketing and online customer reviews, and one dependent variable, which is purchase intention, with perceived value as an intervening variable. The analytical method used is path analysis. Data collection for this research was conducted using a questionnaire filled out by respondents who are students in the city of Pekanbaru and have purchased cosmetic products from Tiktok Shop more than once.The results of the study, based on Partial Tests (t-tests), are as follows: a) There is no significant influence of influencer marketing on perceived value. b) There is a significant influence of online customer reviews on perceived value. c) There is no significant influence of influencer marketing on purchase intention. d) There is a significant influence of online customer reviews on purchase intention. e) There is a significant influence of perceived value on purchase intention. f) Perceived value does not mediate the influence of influencer marketing on purchase intention. g) Perceived value mediates the influence of online customer reviews on purchase intention.